Hedge fund due diligence : - Shain, Randy (Wiley, 2008)
Hedge Fund Due Diligence provides a step-by-step methodology that will allow you to recognize and avoid questionable hedge funds before its too late. Based on a framework that hedge fund investigative expert Randy Shain has refined over the course of his successful career, this book offers an overview of due diligence into hedge fund management, how information on managers can be obtained, and why this information is essential to your investment endeavors